The Politics and Aesthetics of the Urban Commons: Navigating the Gaze of the City, the State, the Market - Volont, Louis (2022)
This thematic issue puts “urban commoning” centre stage. Urban commoning constitutes the practice of sharing urban resources (space, streets, energy, and more) through principles of inclusion and cooperation. Whilst generally defined as an autonomous, bottom‐up, and most of all cooperative practice, the sphere of the commons necessarily stands in interaction with two other spheres: the state/city (“provision”) and the market (“competition”). Yet, the various interlinkages between the commons, the state/city, and the market are underexplored. Hence the rationale for this thematic issue: How does the relation between commons, states/cities, and markets play out in the urban realm? What are the possibilities and pitfalls of linking commons with states/cities and markets? In the first section of this editorial, we provide a substantiated introduction to the concept of the commons, its history, and its urban applications. In the second part, we give an overview of the issue’s contributions. Scholars, activists, and practitioners from the disciplines of urban studies, cultural studies, planning, sustainability, sociology, architecture, and philosophy delve into the uncharted territory between commons, states/cities, and markets, through case studies from the Global North and South. The first three articles delve into the politics of urban commoning while the last three articles illuminate the practice’s aesthetic dimension.